One Health & Risk Management journal promotor of interdisciplinary collaboration and innovative research (One Health & Risk Management, 2024)
As the Deputy Director General in Science of the National Center for Disease Control and Public Health (NCDC) of Georgia, it is my pleasure to acknowledge the launch of the "One Health & Risk Management" journal.Established within the Moldavian Biosafety and Biosecurity Association (MDBBA) in 2019, this journal is a significant step forward in promoting interdisciplinary collaboration and innovative research. Its policy aligns with the latest international concepts advocated by the World Health Organization (WHO), the World Organization for Animal Health (WOAH), and the Food and Agriculture Organization of the United Nations (FAO).In today's complex landscape of global challenges, such as emerging infectious diseases and environmental concerns, there is a growing need for coordinated responses. Thus, the One Health Approach, emphasizing cooperation and transdisciplinary solutions, is more relevant than ever.This journal provides a space for scholars, practitioners, and policymakers to exchange ideas and contribute to the advancement of knowledge. I am confident that "One Health & Risk Management" will play a crucial role in fostering collaboration between international researchers, and bringing diverse perspectives to the forefront.On behalf of the NCDC, I am excited about the launch of this important platform and would like to congratulate the Moldavian colleagues on such an achievement.